2021
DOI: 10.3389/fonc.2021.640268
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Risk Stratification Model to Identify Potential Population Benefiting From Postmastectomy Radiotherapy in T1–2 Breast Cancer With 1–3 Positive Axillary Lymph Nodes

Abstract: Background and ObjectivesTo establish a prognostic stratification nomogram for T1–2 breast cancer with 1–3 positive lymph nodes to determine which patients can benefit from postmastectomy radiotherapy (PMRT).MethodsA population-based study was conducted utilizing data collected from the Surveillance, Epidemiology, and End Results database. Chi-square test or Fisher exact test was used to compare the distribution of characteristics. Cox analysis identified significant prognostic factors for survival. A prognost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…Several retrospective series have found that young patients with T1-2N1 breast cancer have a worse prognosis ( 5 , 20 , 26 , 27 ). However, our analysis demonstrated that patients aged ≥70 years old had worse OS and BCSS, and this finding was similar to that of several previous studies ( 4 , 29 31 ). Hence, the influence of age on the survival of patients with T1-2N1 breast cancer remains controversial, and this observation cannot be explained solely by the higher all-cause mortality rate in patients over 70 years of age.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Several retrospective series have found that young patients with T1-2N1 breast cancer have a worse prognosis ( 5 , 20 , 26 , 27 ). However, our analysis demonstrated that patients aged ≥70 years old had worse OS and BCSS, and this finding was similar to that of several previous studies ( 4 , 29 31 ). Hence, the influence of age on the survival of patients with T1-2N1 breast cancer remains controversial, and this observation cannot be explained solely by the higher all-cause mortality rate in patients over 70 years of age.…”
Section: Discussionsupporting
confidence: 92%
“…Married patients are able to receive more mental and financial support and demonstrate better compliance. Similar findings have recently been reported in patients with T1-2N1 breast cancer ( 4 ). Given the current research situation, we included marital status in the models to explore the relationship between marital status and survival.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, when limited positive SLN were observed, the best treatment for the armpit depends. Based on ACSOG Z0011, AMAROS and OTOASOR study, axillary recurrence (RR) and overall survival (OS) did not differ in patients with low tumor burden and pathologically confirmed 1-2 positive SLN with or without ALND when breast-conserving surgery and radiation were conducted (1,2,4,12,(18)(19)(20)(21)(22)(23). The OTOASOR trial compares completion of axillary lymph node dissection (ALND) to regional nodal irradiation (RNI) in patients with sentinel lymph node metastasis (pN1 SLN) in stage I-II breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively conservative mastectomies, such as skin-sparing mastectomy (SSM) and nipple-sparing mastectomy (NSM), have been widely adopted recently with increasing interest in improved cosmetic outcomes and immediate breast reconstruction [ 1 , 2 ]. With regard to postmastectomy radiation therapy (PMRT), the indications for PMRT were revisited through recent guidelines and studies, including patients with intermediate-risk factors [ [3] , [4] , [5] , [6] , [7] ]. Therefore, adjuvant radiation therapy (RT) following reconstruction has become a common practice [ 8 ].…”
Section: Introductionmentioning
confidence: 99%